37 A weighty issue: nutritional screening in the amau. (5th April 2017) - Murphy, C; Roche, D; Carroll, J; Crosbie, O
Abstract : Background: IrSPEN states that malnutrition affects 145 000 adults at any time in Ireland, especially in chronic illness with >95% of malnourished being community based. HIQA's Report "Review of Nutrition and Hydration Care in Public Acute Hospitals" suggests nutritional assessment within 24 hours of hospitalisation to identify high risk or malnourished patients. In 2011, The Acute Medical Assessment Unit (AMAU), CUH reviewed 5560 patients. Nutritional screening is routinely completed on admitted patients however it was unclear what nutrition details were being recorded on day patients. Aim: To assess if nutritional screening is currently being performed in AMAU day patients. Method: A chart review of 52 consecutive day patient discharges was undertaken examining recording of nutritional screening and weight loss history. Results: 52 consecutive patient charts (19 males, 33 females) were examined with an average age of 53.4 years with an average of 1.46 co-morbidities. Weight was recorded on 36.5% of patients with 26.9% having a hydration status measured. A weight loss history was taken in 19.2% of patients, 40% of which listed weight loss as their presenting complaint. One patient had a BMI completed. A nursing pro-forma in relation to diet consumed was completed in 55.8% of patients. Conclusions: Currently full nutritional screening is not being performed on AMAU day patients. An AMAU patient visit could represent a unique opportunity to nutritionally screen and intervene in high risk multimorbid ill community dwelling day patients. Current barriers to implementation of full nutritional screening include staff shortages, staff training and access to dietetics input if found to be at high risk.